Learning Readiness toward Critical Reasoning Skill of Third Grade Students in Social Science Learning - Cahyaningtyas, Dwi; Ariawan, Vina Anggia Nastitie; Masjid, Akbar Al; Nisa, Ana Fitrotun; Cahyani, Berliana Henu (FKIP Universitas Lampung, 2024)
Learning Readiness toward Critical Reasoning Skill of Third Grade Students in Social Science Learning. Objective: This research aims to analyze the relationship between learning readiness and the critical reasoning skill third grade students in social science learning. Method: This research used quantitative research methods with a correlation research type. The population in the study were third grade elementary school students in Jogonalan sub-district. Meanwhile, the research sample used a convenience sampling technique with a sample size of 30 students. The data validity test used construct validity tests, while the data analysis technique used statistical inference tests. Findings: The research results show that there are students with good learning readiness but whose critical reasoning skill have not yet developed. Then, there are students with moderate learning readiness but whose critical reasoning skill develop as expected. Lastly, there is a linear relationship between good learning readiness and critical reasoning skill which develop as expected. The learning preparation of third grade students obtained an average score of 82 in the good category, while the critical reasoning skill of third grade students obtained an average score of 80 in the developing category. Conclusion: Based on the research results, the researcher concluded that there was a positive relationship between learning readiness and the critical reasoning skill of third grade students in social science learning. Keywords: social science, learning readiness, critical reasoning skill, primary school. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1113-1132